An innovation support system for SMEs - Pereira, João (2018)
Although it is often viewed as a somewhat unpredictable process, the importance of defining clear strategies for innovation is recognized. For this reason, many organizations develop processes that support innovation. In Portugal, the Portuguese Standard 4457: 2007 (NP 4457), which defines the requirements for a Research, Development and Innovation Management System (RDIMS), was introduced in 2007. These requirements act as guidelines for organizations that recognize the importance of innovation. This study aims to create a set of proposals, based on the NP 4457, that support the management of innovation in a small enterprise in the food industry. A case study was carried out in a business environment with a duration of 6 months. In this case study, with an exploratory nature and a qualitative approach, data collection involved documentary analysis, participatory observation and unstructured interviews. After analysing the reality of the company, an Innovation Support System was presented, divided into three components: Strategic Definition, Innovation Process and Evaluation of the Innovation System. The Strategic Definition component has the function of defining the responsibilities and delimiting the scope of innovation for the organization. The Innovation Process includes a set of processes, all the way from the internal and external analysis of the organization, through idea management, evaluation, selection and project management to the final result of the innovation process. Finally, the Evaluation of the system has the function of analysing its performance and proposing improvements. The system proposed here is an attempt to operationalize the recommendations of the Portuguese Standard having in mind the specificities of SMEs. Although it was created for a specific firm, it is based on generic references (such as the Stage-Gate Model or the Chain-linked Interactive Model) and it does not involve specific activities or characteristics of the organization or industry for which it was intended, which makes it possible to adapt it to other SMEs that are interested in improving innovation management performance and/or in the NP 4457 implementation and certification.